2016
DOI: 10.1177/107327481602300404
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Clinical Trial Enrollment in Racial and Ethnic Minority Patients with Cancer

Abstract: Background Clinical trials that study cancer are essential for testing the safety and effectiveness of promising treatments, but most people with cancer never enroll in a clinical trial — a challenge exemplified in racial and ethnic minorities. Underenrollment of racial and ethnic minorities reduces the generalizability of research findings and represents a disparity in access to high-quality health care. Methods Using a multilevel model as a framework, potential barriers to trial enrollment of racial and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
331
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(339 citation statements)
references
References 121 publications
6
331
1
1
Order By: Relevance
“…5 A recent systematic review of cancer clinical trial enrollment in racial/ethnic minorities identified that although the proportion of adult NH Blacks participating in clinical trials increased from 2000-2010, NH Whites continue to comprise the largest majority of participants in these trials. 29 While racial/ethnic disparities have historically persisted in access to medical care and outcomes, there remain significant opportunities to target this underserved population with the reorganization of NCORP sites specifically designated as Minority/Underserved sites. 30 …”
Section: Discussionmentioning
confidence: 99%
“…5 A recent systematic review of cancer clinical trial enrollment in racial/ethnic minorities identified that although the proportion of adult NH Blacks participating in clinical trials increased from 2000-2010, NH Whites continue to comprise the largest majority of participants in these trials. 29 While racial/ethnic disparities have historically persisted in access to medical care and outcomes, there remain significant opportunities to target this underserved population with the reorganization of NCORP sites specifically designated as Minority/Underserved sites. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Adult clinical oncology trials have documented a disparity of racial and ethnic minorities enrolled, as compared with that of the general population. This disparity limits generalization of the research findings and limits access to novel therapies for racial and ethnic minority participants . A similar disparity of enrollment, albeit to a lesser degree, exists among racial minority participants in pediatric clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…Although language and cultural barriers have been found to impact on trial participation by CALD patients in overseas trials, 6 our analysis suggests language barriers are particularly problematic. CALD patients whose preferred language is not English may be less likely to participate in trials for several reasons.…”
Section: Barriers To Trial Participationmentioning
confidence: 60%